2018
DOI: 10.1002/asi.24015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the use of social network sites on users' psychological well‐being: A systematic review

Abstract: As Social Network Sites (SNSs) are increasingly becoming part of people's everyday lives, the implications of their use need to be investigated and understood. We conducted a systematic literature review to lay the groundwork for understanding the relationship between SNS use and users' psychological well-being and for devising strategies for taking advantage of this relationship. The review included articles published between 2003 and 2016, extracted from major academic databases. Findings revealed that the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 62 publications
1
63
0
6
Order By: Relevance
“…It is important to note here that other reviews have highlighted positive effects of social media. Some find that social media increases well-being, social communication, social support, social capital, authentic self-presentation and social connectedness while decreasing lonelinesseven though these reviews routinely note that other studies have found exactly the opposite [20]. One review concluded that those users who go to Facebook to promote social support and connection show lower levels of depressive symptoms [24].…”
Section: Systematic Reviews and Meta-analyses: Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note here that other reviews have highlighted positive effects of social media. Some find that social media increases well-being, social communication, social support, social capital, authentic self-presentation and social connectedness while decreasing lonelinesseven though these reviews routinely note that other studies have found exactly the opposite [20]. One review concluded that those users who go to Facebook to promote social support and connection show lower levels of depressive symptoms [24].…”
Section: Systematic Reviews and Meta-analyses: Social Mediamentioning
confidence: 99%
“…Furthermore, there needs to be an increased focus on individual differences. This would be helped by the study of more diverse and rigorously recruited samples, as much of the current research is conducted on convenience samples or populations in the global north [20]. More studies should also account for factors like gender or age.…”
Section: At-risk Populationsmentioning
confidence: 99%
“…In brief, emphasizing the digitally networked nature of the self seems to be at odds with the previous idea of the self as a discrete, coherent entity [90]. Furthermore, there is some evidence that the newer conceptualization of the self undermines psychological well-being [94,95]. Naturally, people experiencing tension in their self-concept seek to resolve that tension.…”
Section: Implications For Identitymentioning
confidence: 99%
“…Speaking to the crisis of meaning more generally, others have discussed how people today, beset by information overload and enthralled by on-demand culture, feel distracted and unable to engage deeply with the world (Lanier, 2018;Pentina & Tarafdar, 2014). A review of the empirical literature on social networking sites and psychological well-being by Erfani and Abedin (2018) shows that, while studies reporting on such negative effects constitute a minority of the literature, such findings have been validated.…”
Section: Perfectionism and The Crisis Of Meaningmentioning
confidence: 99%